Preserved amniotic membrane transplantation for conjunctival surface reconstruction - Pinnita Prabhasawat (2018)
Objective. To study the efficacy of preserved human amniotic membrane in the reconstruction of conjunctival defect created during surgical removal of conjunctival lesions or symblepharon lysis. Methods. Preserved human amniotic membrane transplantation was performed in 93 eyes of 85 patients for reconstruction of various conjunctival surface problems. The indications for surgery were (1) pterygium excision (54 eyes), (2) conjunctival tumors excision (23 eyes), lysis of symblepharon (13 eyes), and covering a scleral graft (three eyes). Results. Success was noted in 69.9% (65/93) eyes, partially success in 22.6% (21/93) eyes, and failure in 7.5% (7/93) eyes with a mean follow-up of 8.9 months (1-28 months). In pterygium, conjunctival tumor, symblepharon, and scleral graft group, the success rate in each group was 70.3%, 78.3%, 53.8%, and 66.7% respectively. No serious immediate post-operative complications or graft rejection occurred. Conclusion. Amniotic membrane transplantation can be considered an alternative treatment for difficult ocular surface problems, and is effective in promoting epithelial healing, and reducing inflammation and scarring.